Effect of Binaural Stimulation on Attention and EEG - CRESPO, Adela; RECUERO, Manuel; GALVEZ, Gerardo; BEGONA, Adrian (Archives of Acoustics, 2013)
When two pure tones of slightly different frequency are presented separately to each ear, the listener perceives a third single tone with amplitude variations at a frequency that equals the difference between the two tones; this perceptual illusion is known as the binaural auditory beat (BB). There are anecdotal reports that suggest that the binaural beat can entrain EEG activity and may affect the arousal levels, although few studies have been published. There is a need for double-blind, well-designed studies in order to establish a solid foundation for these sounds, as most of the documented benefits come from self-reported cases that could be affected by placebo effect. As BBs are a cheap technology (it even exists a free open source programmable binaural- beat generator on the Internet named Gnaural), any achievement in this area could be of public interest. The aim in our research was to explore the potential of BBs in a particular field: tasks that require focus and concentration. In order to detect changes in the brain waves that could relate to any particular improvement, EEG recordings of a small sample of individuals were also obtained. In this study we compare the effect of different binaural stimulation in 7 EEG frequency ranges. 78 participants were exposed to 20-min binaural beat stimulation. The effects were obtained both quali- tative with cognitive test and quantitative with EEG analysis. Results suggest no significant statistical improvement in 20-min stimulation.